2016
DOI: 10.1016/j.vaccine.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to timely administration of birth dose vaccines in The Gambia, West Africa

Abstract: ObjectiveAlthough vaccine coverage in infants in sub-Saharan Africa is high, this is estimated at the age of 6–12 months. There is little information on the timely administration of birth dose vaccines. The objective of this study was to assess the timing of birth dose vaccines (hepatitis B, BCG and oral polio) and reasons for delayed administration in The Gambia.MethodsWe used vaccination data from the Farafenni Health and Demographic Surveillance System (FHDSS) between 2004 and 2014. Coverage was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 33 publications
8
100
6
Order By: Relevance
“…Forty-eight articles met all inclusion criteria for this study; 28 articles were excluded for various reasons. [See supplementary materials 3] Nine articles employed second-hand data analysis [7,12,18,27,37,40,41,47,42]; thirty-six used cross-sectional design [1-3, 11, 13-17, 19, 21-26, 28-36, 38-39, 42, 45-46, 48-51, 53, 54] and three used case-control study [20,[43][44]. All described studies were conducted on Africa populations (103,655 adults and 76,327 children).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-eight articles met all inclusion criteria for this study; 28 articles were excluded for various reasons. [See supplementary materials 3] Nine articles employed second-hand data analysis [7,12,18,27,37,40,41,47,42]; thirty-six used cross-sectional design [1-3, 11, 13-17, 19, 21-26, 28-36, 38-39, 42, 45-46, 48-51, 53, 54] and three used case-control study [20,[43][44]. All described studies were conducted on Africa populations (103,655 adults and 76,327 children).…”
Section: Resultsmentioning
confidence: 99%
“…The place of delivery of a baby was reported as determinants of full immunization of a child. Delivery at health facility enhances full immunization [18,20,22,27,28,40,48]. Long waiting time at health facilities was frequently and consistency noted [11,12,31,35,36,45].…”
Section: Resultsmentioning
confidence: 99%
“…Miyahara et al [30] found that vaccination by day 7 was associated with living in urban areas (west rural: (OR = 1.42, 95%CI 1.06 -1.89), but there was no effect of the age of the mother [31]. Globally, most authors agree that the socioeconomic and educational levels have an influence on the lack of knowledge of TB and vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even in countries that integrated BDV, studies have revealed the lack of compliance with the timeliness. For example, a study in the Gambia found that, between 2004 and 2014, despite BDV being part of the EPI, only 1.1% of newborns received their first dose of hepatitis B vaccine within 24 hours of birth, 5.4% by day 7 and 58.4% by day 28 . This finding was replicated by another study, which found that only 7% of Gambian infants received timely BDV, and the median time to ‘birth dose’ vaccination was 11 days (IQR 6‐16 days) …”
Section: Interventions To Prevent Mother‐to‐child Transmission Of Hbvmentioning
confidence: 93%